Areas of Technological Transvaluation through Deleuze-Guattari’s Philosophy - Cebral Loureda, Manuel Cebral (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2019)
The philosophy of Deleuze and Guattari is used both to encourage the current technological and cybernetic evolution of society and to the contrary: to proclaim the need for areas and opaque layers to interconnectivity. Probably this is because technology itself is neutral: it depends on our uses and applications, the type of social formations that it gives rise to. But, if we contrast the current uses and applications, which areas would be the most critical, those in which there is more sensitively a transvaluation of the use of technologies? Four axes are proposed around which we critically decide the human and social use of technology.